Molecular interaction of natural dye based onZea mays andBixa orellanawith nanocrystalline TiO2in dye sensitized solar cells - Huamán Aguirre, Arnold Anthony (2021)
This work studies the interaction between natural dyes obtained from Peruvian Zea mays and Bixa orellana seeds and nanostructured titanium dioxide, in order to evaluate their function as sensitizers into solar cell devices. The effective attachment of dyes to the TiO2 layer is corroborated by the comparison of UV-Visible absorption and FT-IR spectra of the extracted dye solutions and sensitized TiO2 electrodes. The principal compounds from the seed extraction of Zea mays and Bixa orellana are cyanidin-3-glucoside (C3G) and bixin respectively, which were analyzed in an isolated dye/cluster TiO2 system by molecular dynamic simulation. The results showed that chemisorption is carried out through a consecutive deprotonation process, and Ti-O bond formation by the monodentate OH and COOH anchoring groups, for C3G and bixin respectively. Finally, we tested the effect of the dye – TiO2 interaction on the charge transfer by the comparison of the current-voltage curves and incident photon-to-current conversion efficiency (IPCE) of the cells. We found that dye agglomeration in films with Bixa orellana and high charge recombination of films with Zea mays are critical points to be solved. For this reason, we propose the pretreatment of the TiO2 film before sensitization with Bixa orellana and analyze the effects of pH in Zea mays solution, in order to obtain better device efficiencies.